Nawāwī al-Bantānī: An Intellectual Master of the Pesantren Tradition - Abd Rahman (Studia Islamika, 1996)
Nawawi al-Bantani is one of Indonesia's most prominent scholars in the 19th century. Due to the depth of his knowledge, he never holds the status as Haramayn priest, who taught in Mecca and Medina, as well as been invited to attend and give a talk in a kind of religious discussion in the University al-Azhar, Cairo. He is a very prolific writer who produced more than 100 works in at least nine fields of Islamic sciences: interpretation, fiqh, usul al-din, 'ilm tawhid, tasawwuf, the Prophet's history, Arabic grammar, hadith, and Morals. This paper describes that the emergence of al-Banteni as great scholars closely associated with Islamic tradition and to talk briefly about the views of al-Banteni in four areas: interpretation, Sufism and morals, Islamic law, and Tawhid.DOI: 10.15408/sdi.v3i3.801